Il corpo della parola. Alle origini del piacere di narrare - Gamelli, Ivano (Studi sulla Formazione/Open Journal of Education, 2017)
There is an evolutionary link between what Piaget called the ‘’action” and the narrative - the “first interpretative and cognitive device of which man uses in his life experience” (Bruner, 1992). Also for Piaget, the action (movement) and thinking are “isomorphic”, as in child development leads in the other one o’clock: the thought is internalized action. The essay will decline this transition - crucial for everyone involved in early learning (but not only) - as we now know (thanks to new contributions that come from the neuroscience studies) that many of the difficulties and problems that do not few and a few boys and girls meet in the transition to a symbolic level, for example in the learning of reading and writing, have their roots in a lack of or insufficient experienced sensorimotor sacrificed by an early ipercognitivizzazione where today many preschools and early the primary cycle seem to favor. Building on the awareness of the infant Research of reflexive and operational contributions of the body of the pedagogy and practice psychomotor, this pedagogical reflection traces a thread that connects the primary pleasure of movement to the pleasure of narrating, outlining some useful ideas for setting configuration training capable of allowing children an educational experience respectful of their bodies, space, time, relations.